Enabling liquid solvent structure analysis using hard x-ray absorption spectroscopy with a transferrable microfluidic reactor. (11th April 2018) - Zheng, Jian; Zhang, Wei; Wang, Feng; Yu, Xiao-Ying
Abstract: In this paper, a vacuum compatible microfluidic device, system for analysis at the liquid vacuum interface, is integrated to hard x-ray absorption spectroscopy to obtain the local structure of K3 [Fe(CN)6 ] in aqueous solutions with three concentrations of 0.5 M, 0.05 M, and 0.005 M. The solutions were sealed in a microchannel 500 µ m wide and 300 µ m deep in a portable microfluidic device. The Fe K -edge x-ray absorption spectra indicate a presence of Fe(III) in the complex in water, with an octahedral geometry coordinated with 6 C atoms in the first shell with a distance of ~1.92 Å and 6 N atoms in the second shell with a distance of ~3.10 Å. Varying the concentration has no observable influence on the structure of K3 [Fe(CN)6 ]. Our results demonstrate the feasibility of using microfluidic based liquid cells in large synchrotron facilities. Using portable microfludic reactors provides a viable approach to enable multifaceted measurements of liquids in the future.